Improvements in occupational satisfaction, self-efficacy and subjective QOL resulting from a change from “performance” to “engagement” in meaningful occupations by occupation-centered individual rehabilitation: A practical report of a patient with cerebral hemorrhage sequelae admitted to a psychiatric hospital - Nagai, Misaki; Tokumitsu, Kenichi; Imamoto, Yusuke (Japanese Occupational Therapy Research, 2024)
Occupation-centered individualized rehabilitation based on the Occupational Therapy Intervention Process Model (OTIPM) was performed for a schizophrenic patient with sequelae of cerebral hemorrhage. As physical function declined and pain worsened, the focus of intervention shifted from “performance” to “engagement.” The intervention resulted in an improvement of satisfaction from 3.3 to 6.7 in the Canadian Occupational Performance Measure（COPM）, a self-efficacy deviation from 34 to 37, and a mean subjective increase of the World Health Organization Quality of Life assessment (WHOQOL) from 2.27 to 2.31. This suggests that proving engagement-focused interventions to patients who have difficulty in occupational performance is one effective approach that contributes to a healthy life with a sense of oneself.